2011
DOI: 10.1371/journal.pone.0018014
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Prn Variation in the Mouse Model and Comparison with Epidemiological Data

Abstract: The virulence factor pertactin (Prn) is a component of pertussis vaccines and one of the most polymorphic Bordetella pertussis antigens. After the introduction of vaccination shifts in predominant Prn types were observed and strains with the Prn vaccine type (Prn1) were replaced by strains carrying non-vaccine types (Prn2 and Prn3), suggesting vaccine-driven selection. The aim of this study was to elucidate the shifts observed in Prn variants. We show that, although Prn2 and Prn3 circulated in similar frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 49 publications
3
22
1
Order By: Relevance
“…Prn has been shown to facilitate adhesion and resistance of B. pertussis to neutrophil-mediated clearance [25,30]. Previous studies have indicated that Prn knockouts were less efficient in colonising the mouse lungs [24]. Our results confirmed these observations.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prn has been shown to facilitate adhesion and resistance of B. pertussis to neutrophil-mediated clearance [25,30]. Previous studies have indicated that Prn knockouts were less efficient in colonising the mouse lungs [24]. Our results confirmed these observations.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study by van Gent et al showed that the prn knock-out mutant had decreased ability to colonise the trachea and lungs in mice, but complementation of the prn knock-out mutant restored this ability [24]. In B. bronchiseptica, Prn also plays a role in resistance to neutrophil-mediated clearance, promoting persistence in the lower respiratory tract [25].…”
Section: Introductionmentioning
confidence: 99%
“…Polak et al showed that strains carrying ptxA1/ptxP1/prn2 colonised better than ptxA1/ ptxP1/prn1 or ptxA1/ptxP1/prn3 strains at day 14 post-challenge in mice, suggesting better fitness of strains with prn2 allele [36]. In contrast, van Gent et al showed in naïve mice that the prn1 strain colonised significantly better than prn2 or prn3 strains suggesting better fitness of prn1 strains [37].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that B. pertussis Prn − mutants colonized less well than Prn + strains in mice [18]. It is also known that Prn prevents either bacterial adherence or internalization or both, to human monocyte-derived dendritic cells [30] and that it also plays a role in resistance to neutrophil-mediated clearance [31].…”
Section: Discussionmentioning
confidence: 99%